2015
DOI: 10.1038/ncomms8743
|View full text |Cite|
|
Sign up to set email alerts
|

MEG3 long noncoding RNA regulates the TGF-β pathway genes through formation of RNA–DNA triplex structures

Abstract: Long noncoding RNAs (lncRNAs) regulate gene expression by association with chromatin, but how they target chromatin remains poorly understood. We have used chromatin RNA immunoprecipitation-coupled high-throughput sequencing to identify 276 lncRNAs enriched in repressive chromatin from breast cancer cells. Using one of the chromatin-interacting lncRNAs, MEG3, we explore the mechanisms by which lncRNAs target chromatin. Here we show that MEG3 and EZH2 share common target genes, including the TGF-β pathway genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
601
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(627 citation statements)
references
References 70 publications
(94 reference statements)
25
601
0
1
Order By: Relevance
“…Recently, ChIRP-seq and similar approaches have been used to demonstrate that lncRNAs are able to physically bind DNA in a genome-wide fashion, partly through the presence of AG-purine-rich stretches acting as putative lncRNA-binding motifs (30,53). In our own ChIRP-seq analysis, we found that ChIP-qPCR analysis of PGC-1α in control WT (Ctrl) and Tug1-KD cells at the upstream TBE element, an intergenic region devoid of the predicted PGC-1α interaction, and the Ppargc1a gene promoter (primers spanning the distal, medial, and proximal regions of the promoter).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, ChIRP-seq and similar approaches have been used to demonstrate that lncRNAs are able to physically bind DNA in a genome-wide fashion, partly through the presence of AG-purine-rich stretches acting as putative lncRNA-binding motifs (30,53). In our own ChIRP-seq analysis, we found that ChIP-qPCR analysis of PGC-1α in control WT (Ctrl) and Tug1-KD cells at the upstream TBE element, an intergenic region devoid of the predicted PGC-1α interaction, and the Ppargc1a gene promoter (primers spanning the distal, medial, and proximal regions of the promoter).…”
Section: Methodsmentioning
confidence: 99%
“…MEG3 modulates the activity of TGF-β genes by binding to distal regulatory elements forming an RNA-DNA triplex and interacts with the PRC2 complex (Mondal, et al 2015). PCAT1 is the most highly upregulated lncRNA in PCa (Alahari et al 2016).…”
Section: Lncrnas In Prostate Tumorsmentioning
confidence: 99%
“…Similarly, the lncRNA Linc00617 has been found to have oncogenic activity in breast cancer (10). Furthermore, oncogenic lncRNA maternally expressed 3 regulates the tumor growth factor-β signaling pathway via the formation of RNA-DNA triplex structures (11).…”
Section: Introductionmentioning
confidence: 99%